The association between the uric acid-to-high-density lipoprotein cholesterol ratio and osteoarthritis risk in U.S. adults: a cross-sectional study based on NHANES 1999–2016 - Yaoxin Ao; Fangjun Xiao; Junpeng Qiu; Jiangfeng Lyu; Wenli Luo; Yifei Liufu; Junxing Yang (Lipids in Health and Disease)
Abstract Objective The uric acid-to-high-density lipoprotein cholesterol ratio (UHR) is an established biomarker for metabolic and inflammatory disorders but has received little attention in relation to osteoarthritis (OA). This investigation examines the UHR‒OA risk correlates. Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) 1999–2016. Descriptive analyses, univariate and multivariate logistic regression models, as well as generalized additive and segmented regression models were used to investigate the nonlinear correlation and threshold effect of UHR-OA. Results A total of 20,727 U.S. adults were included, 2,900 of whom (13.99%) were diagnosed with osteoarthritis (OA). A nonlinear relationship with a significant threshold effect was observed between the UHR and OA. When the UHR was less than 0.109, it was strongly inversely related to OA (OR = 0.028, 95% CI: 0.002–0.345, P < 0.01). The odds ratio increased when the UHR surpassed 0.109 but was not statistically significant (OR = 0.625, 95% CI: 0.162–2.421, P > 0.05). According to the unadjusted logistic regression model, the UHR was not significantly correlated with OA (P > 0.05). Following adjustment for confounders, including sex, age, ethnicity, education, marriage, BMI, income, hypertension, diabetes, coronary heart disease, and hypercholesterolemia, a notable inverse relationship emerged (OR = 0.259, 95% CI: 0.093–0.718, P < 0.01). Univariate linear regression studies revealed an intense inverse relationship between UA and HDL-C (OR = -3.2, 95% CI: -3.3 to -3.0, P < 0.001). In addition, stratified studies revealed that the negative relationships between the UHR and OA were more pronounced in elderly individuals (≥ 50 years old), women, drinkers, non-Hispanic whites, individuals with higher education levels and individuals without metabolic disorders (those with no hypertension, diabetes, coronary heart disease, or hypercholesterolemia) and did not show obvious heterogeneity in smoking status, BMI, marriage, or income level. Conclusions This study revealed a nonlinear relationship between the UHR and OA, with a threshold at UHR = 0.109. Below this level, the UHR was significantly negatively associated with OA, especially in older adults (≥ 50 years old), females, drinkers, non-Hispanic Whites, and those with an education level above high school, or no metabolic diseases.